2019
DOI: 10.5334/egems.246
|View full text |Cite
|
Sign up to set email alerts
|

Defining High Value Elements for Reducing Cost and Utilization in Patient-Centered Medical Homes for the TOPMED Trial

Abstract: Introduction: Like most patient-centered medical home (PCMH) models, Oregon’s program, the Patient-Centered Primary Care Home (PCPCH), aims to improve care while reducing costs; however, previous work shows that PCMH models do not uniformly achieve desired outcomes. Our objective was to describe a process for refining PCMH models to identify high value elements (HVEs) that reduce cost and utilization. Methods: We performed a targeted literature review of each PCPCH core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 47 publications
(74 reference statements)
0
8
1
Order By: Relevance
“…Our previous work from this study has shown promise in improving the patient experience of care and in engaging practices in transformation. 26,35 This study, however, did not show clear benefits to cost and utilization. The ability to change individual trajectories of patients' health with PCMH and advanced primary care models may be limited without organizationally focused team-driven and patient-driven approaches; programs that facilitate structured care planning with clear tailoring and patient-directed goal setting may also overcome the challenges found in this work.…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“…Our previous work from this study has shown promise in improving the patient experience of care and in engaging practices in transformation. 26,35 This study, however, did not show clear benefits to cost and utilization. The ability to change individual trajectories of patients' health with PCMH and advanced primary care models may be limited without organizationally focused team-driven and patient-driven approaches; programs that facilitate structured care planning with clear tailoring and patient-directed goal setting may also overcome the challenges found in this work.…”
Section: Discussioncontrasting
confidence: 58%
“…Previous results from this trial showed improvement in patient experience of care29 and no change in teamwork and adaptive reserve across the clinics 35. This result was despite significant engagement in the model and improvement in both the HVEs and other QI metrics 26. The time-based modeling showed promising decreases over time, indicating a longer time window may have show different results.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations